1990
DOI: 10.1097/00000658-199006000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Early Burn Wound Excision Significantly Reduces Blood Loss

Abstract: The hypothesis that near-total early excision of large burns in children can be performed safely with a reduction in blood loss was tested. Of 1662 acutely burned patients admitted to this institution between 1982 and 1989, 594 underwent near-total excision of cutaneous flame or scald burn injuries in a single procedure. Operations took less than 3 hours and there were no operative deaths. Blood losses in burns of more than 30% total body surface area (TBSA) were significantly less at 0.40 +/- 0.06 mL/cm2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
1
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(63 citation statements)
references
References 32 publications
1
58
1
3
Order By: Relevance
“…Early excision of burn wounds has been shown, by our institution and others, to directly benefit patients through reducing blood loss at operation, 28 decreasing overall hospital stay, 29 and limiting serious infectious complications, 30,31 but has not previously been shown to alter the metabolic response. 32 The association between burn-induced hypermetabolism and muscle wasting has been controversial.…”
Section: Discussionmentioning
confidence: 85%
“…Early excision of burn wounds has been shown, by our institution and others, to directly benefit patients through reducing blood loss at operation, 28 decreasing overall hospital stay, 29 and limiting serious infectious complications, 30,31 but has not previously been shown to alter the metabolic response. 32 The association between burn-induced hypermetabolism and muscle wasting has been controversial.…”
Section: Discussionmentioning
confidence: 85%
“…3,21 We believe that the use of this surgical approach in our patient population is primarily responsible for the low death rate in the patients who survived more than 30 days after the burn. Survival in the overall population with burns of more than 90% TBSA was also improved by this technique.…”
Section: Discussionmentioning
confidence: 97%
“…33,34 Recent studies by Herndon and associates have shown that burn wound excision reduced blood loss, reduced mortality, and improved wound healing. 21,35 If indeed the burn wound provides a potential source of inflammatory mediators, early removal of this damaged tissue would be expected to interrupt inflammatory cell signaling, to reduce proinflammatory cytokine synthesis, to improve downstream organ function, and to decrease susceptibility to subsequent infection. Studies described herein support that premise.…”
Section: Discussionmentioning
confidence: 99%
“…14 -17 However, cutaneous burns and loss of the dermal barrier renders the burn subject susceptible to bacterial invasion via the burn wound; in this regard, Barret and Herndon showed greater bacterial colonization of the burn wound bed and increased rates of infection with delayed burn wound excision. 18 Numerous other studies have described that early excision of the burn wound modulated systemic inflammatory cytokine responses to burn injury, 19 attenuated muscle catabolism, 20 decreased operative blood loss, 21 decreased length of hospitalization, and decreased the incidence of wound infection. 22 However, the effects of early burn wound excision on myocardial inflammation and dysfunction have not, to our knowledge, been studied.…”
mentioning
confidence: 99%